Author 
Message 
TAGS:

Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 59147

If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
15 Mar 2018, 23:03
Question Stats:
84% (01:38) correct 16% (01:32) wrong based on 61 sessions
HideShow timer Statistics
If d = (c  b)/(a  b), then b = A. (c  d)/(a  d) B. (c + d)/(a + d) C. (ca  d)/(ca + d) D. (c  ad)/(1  d) E. (c + ad)/(d 1)
Official Answer and Stats are available only to registered users. Register/ Login.
_________________



Senior PS Moderator
Joined: 26 Feb 2016
Posts: 3308
Location: India
GPA: 3.12

If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
16 Mar 2018, 01:07
Bunuel wrote: If d = (c  b)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) We are given that d = \(\frac{cb}{ab}\) Cross multiplying, da  db = c  b \(db  b = c  ad\) > \(b(d  1) = c  ad\) > \(b = \frac{(c  ad)}{(d  1)}\) Therefore, b = \(\frac{(c  ad)}{(d  1)}\) (Option D)Alternate approach
If c=4,b=1,a=2 then d=41/21 = 3 Now substutiting in the available answer options, A. (c  d)/(a  d) = (43)/(23) = ive
B. (c + d)/(a + d) = (4+3)/(2+3) = 7/5
C. (ca  d)/(ca + d) = (83)/(8+3) = 5/11D. (c  ad)/(1  d) = (46)/(13) = 2/2 = 1 E. (c + ad)/(d 1) = (4+6)/2 = 10/2 = 5 (Option D)
_________________
You've got what it takes, but it will take everything you've got



Math Expert
Joined: 02 Sep 2009
Posts: 59147

Re: If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
15 Mar 2018, 23:04
Bunuel wrote: If d = (c  a)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) 7. Algebra Check below for more: ALL YOU NEED FOR QUANT ! ! !Ultimate GMAT Quantitative Megathread
_________________



CEO
Status: GMATINSIGHT Tutor
Joined: 08 Jul 2010
Posts: 2977
Location: India
GMAT: INSIGHT
WE: Education (Education)

Re: If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
16 Mar 2018, 00:53
Bunuel wrote: If d = (c  a)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) d = (c  a)/(a  b) i.e. (ab) = (ca)/d i.e. b = a  (ca)/d i.e. b = [ad  (ca)]/d Bunuel Are the options correct???
_________________
Prosper!!!GMATinsightBhoopendra Singh and Dr.Sushma Jha email: info@GMATinsight.com I Call us : +919999687183 / 9891333772 Online OneonOne Skype based classes and Classroom Coaching in South and West Delhihttp://www.GMATinsight.com/testimonials.htmlACCESS FREE GMAT TESTS HERE:22 ONLINE FREE (FULL LENGTH) GMAT CAT (PRACTICE TESTS) LINK COLLECTION



Math Expert
Joined: 02 Sep 2009
Posts: 59147

Re: If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
16 Mar 2018, 01:03
GMATinsight wrote: Bunuel wrote: If d = (c  a)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) d = (c  a)/(a  b) i.e. (ab) = (ca)/d i.e. b = a  (ca)/d i.e. b = [ad  (ca)]/d Bunuel Are the options correct??? There was a typo: it's d = (c  b)/(a  b) NOT d = (c  a)/(a  b). Edited. Thank you for noticing!
_________________



CEO
Status: GMATINSIGHT Tutor
Joined: 08 Jul 2010
Posts: 2977
Location: India
GMAT: INSIGHT
WE: Education (Education)

Re: If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
16 Mar 2018, 01:09
Bunuel wrote: If d = (c  b)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) d = (c  b)/(a  b) i.e. da  bd = cb i.e. bd  b = da  c i.e. b (d1) = dac i.e. b = (da  c) / (d1) or b = (c  ad)/(1  d) Answer: option D
_________________
Prosper!!!GMATinsightBhoopendra Singh and Dr.Sushma Jha email: info@GMATinsight.com I Call us : +919999687183 / 9891333772 Online OneonOne Skype based classes and Classroom Coaching in South and West Delhihttp://www.GMATinsight.com/testimonials.htmlACCESS FREE GMAT TESTS HERE:22 ONLINE FREE (FULL LENGTH) GMAT CAT (PRACTICE TESTS) LINK COLLECTION



Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 8415
Location: United States (CA)

Re: If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
19 Mar 2018, 16:14
Bunuel wrote: If d = (c  b)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) First, we multiply both sides by (a  b) and expand the left side: d(a  b) = c  b da  db = c  b Now, since our goal is to solve for b, we put all terms containing b on the left side of the equation and all other terms on the right side: b  db = c  da On the left side of the equation, factor out the common factor b from both terms: b(1  d) = c  da Divide both sides by (1  d), and now b is by itself on the left side of the equation: b = (c  da)/(1  d) Answer: D
_________________
5star rated online GMAT quant self study course See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews If you find one of my posts helpful, please take a moment to click on the "Kudos" button.



Intern
Joined: 07 Jul 2017
Posts: 1

If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
19 Mar 2018, 19:32
pushpitkc wrote: Bunuel wrote: If d = (c  b)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) We are given that d = \(\frac{cb}{ab}\) Cross multiplying, da  db = c  b \(db  b = c  ad\) > \(b(d  1) = c  ad\) > \(b = \frac{(c  ad)}{(d  1)}\) Therefore, b = \(\frac{(c  ad)}{(d  1)}\) (Option D)Alternate approach
If c=4,b=1,a=2 then d=41/21 = 3 Now substutiting in the available answer options, A. (c  d)/(a  d) = (43)/(23) = ive
B. (c + d)/(a + d) = (4+3)/(2+3) = 7/5
C. (ca  d)/(ca + d) = (83)/(8+3) = 5/11D. (c  ad)/(1  d) = (46)/(13) = 2/2 = 1 E. (c + ad)/(d 1) = (4+6)/2 = 10/2 = 5 (Option D)I understand the algebraic approach, but I can not get alternative approach. Using your variables I arrived at the correct answer, but when I use the variables a=1 , b=2, c=3, and d=1, I get answer A and D equal to 2. Why can I not use this set of variables?



Intern
Joined: 04 Aug 2014
Posts: 2

Re: If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
20 Mar 2018, 00:52
ScottTargetTestPrep wrote: Bunuel wrote: If d = (c  b)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) First, we multiply both sides by (a  b) and expand the left side: d(a  b) = c  b da  db = c  b Now, since our goal is to solve for b, we put all terms containing b on the left side of the equation and all other terms on the right side: b  db = c  da On the left side of the equation, factor out the common factor b from both terms: b(1  d) = c  da Divide both sides by (1  d), and now b is by itself on the left side of the equation: b = (c  da)/(1  d) Answer: D I can follow your manipulations once I see the solution but how did you know  in two minutes  those were the right manipulations to get to the answer choices?.. I got stuck with b=cda+db (which is correct but does not correspond to any answer choices...).



Manager
Joined: 28 Jan 2018
Posts: 50
Location: Netherlands
Concentration: Finance
GPA: 3

If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
20 Mar 2018, 10:25
Bunuel wrote: If d = (c  b)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) \(d\) = \(\frac{(cb)}{(ab)}\) => \(d(a  b) = c  b\) => \(ad  bd = c  b\) => \(b  bd = c  ad\) => \(b(1  d) = c  ad\) => \(b\) = \(\frac{(cad)}{(1d)}\) Answer (D)



Manager
Joined: 28 Jan 2018
Posts: 50
Location: Netherlands
Concentration: Finance
GPA: 3

Re: If d = (c  b)/(a  b), then b =
[#permalink]
Show Tags
20 Mar 2018, 10:27
grgsky wrote: ScottTargetTestPrep wrote: Bunuel wrote: If d = (c  b)/(a  b), then b =
A. (c  d)/(a  d)
B. (c + d)/(a + d)
C. (ca  d)/(ca + d)
D. (c  ad)/(1  d)
E. (c + ad)/(d 1) First, we multiply both sides by (a  b) and expand the left side: d(a  b) = c  b da  db = c  b Now, since our goal is to solve for b, we put all terms containing b on the left side of the equation and all other terms on the right side: b  db = c  da On the left side of the equation, factor out the common factor b from both terms: b(1  d) = c  da Divide both sides by (1  d), and now b is by itself on the left side of the equation: b = (c  da)/(1  d) Answer: D I can follow your manipulations once I see the solution but how did you know  in two minutes  those were the right manipulations to get to the answer choices?.. I got stuck with b=cda+db (which is correct but does not correspond to any answer choices...). hi, ideally in these kind of questions, you'll want to concentrate all the value that related to b on one side of the equation and the rest on the other side. Check my solution above for details




Re: If d = (c  b)/(a  b), then b =
[#permalink]
20 Mar 2018, 10:27






